Pengembangan Sistem Informasi Tracer Study Fakultas Ilmu Komputer Universitas Brawijaya Menggunakan Metode Rational Unified Procces - Sholachuddin Al Ayubi; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Do data collection when entering working world is sould be done in every study program. The graduate that can get the corresponding job with areas of expertise wich are owned can help study program to get the relevan suggestion. Not only that, but every study program also be accused to have good accreditation. One of parameter accreditation rating is follow up the graduate tracking. but the big case is almous data is hard file, so need more procces to get the data. In fact the proccess to get the data is longer. To solve this problem is need one best sistem that can doing the data while classify the management data of graduate. Rational Unified Proccess (RUP) is development method sistem that chosen, because on this all changed controll proccess can do in every step. So make it easy to correct fastly n have a good dokumentation. RUP have some stage, such as inception, elaboration, construction and transition. Testing proccess sistem is doing with some method. such as blackbox testing, compatibility testing serta user acceptance testing. The result of test UAT get score 90% from all the graduate that traying this sistem. The system that has been worked on is able to answer the data collection problems experienced by FILKOM's students. so data collection becomes easier. the conclution is tracer information sistem is received well by sistem user.